Developments and challenges of FLT3 inhibitors in acute myeloid leukemia - Ge, Shuai-Shuai; Liu, Song-Bai; Xue, Sheng-Li (Frontiers in Oncology, 2022)
FLT3 mutations are one of the most common genetic alterations in acute myeloid leukemia (AML) and are identified in approximately one-third of newly diagnosed patients. Aberrant FLT3 receptor signaling has important implications for the biology and clinical management of AML. In recent years, targeting FLT3 has been a part of every course of treatment in FLT3-ITD/TKD-mutated AML and contributes to substantially prolonged survival. At the same time, wide application of next-generation sequencing (NGS) technology has revealed a series of non-canonical FLT3 mutations, including point mutations and small insertions/deletions. Some of these mutations may be able to influence downstream phosphorylation and sensitivity to FLT3 inhibitors, while the correlation with clinical outcomes remains unclear. Exploration of FLT3-targeted therapy has made substantial progress, but resistance to FLT3 inhibitors has become a pressing issue. The mechanisms underlying FLT3 inhibitor tolerance can be roughly divided into primary resistance and secondary resistance. Primary resistance is related to abnormalities in signaling factors, such as FL, CXCL12, and FGF2, and secondary resistance mainly involves on-target mutations and off-target aberrations. To overcome this problem, novel agents such as FF-10101 have shown promising potential. Multitarget strategies directed at FLT3 and anomalous signaling factors simultaneously are in active clinical development and show promising results.